Salicylic Acid and Nitric Oxide: Insight Into the Transcriptional Regulation of Their Metabolism and Regulatory Functions in Plants - Rai, Krishna Kumar; Pandey, Neha; Rai, Nagendra; Rai, Sanjay Kumar; Pandey-Rai, Shashi (Frontiers in Agronomy, 2021)
Salicylic acid (SA) and nitric oxide (NO) are key signaling molecules required to activate the plant's innate immunity against abiotic stresses and biotrophic attackers. Stress-induced signaling and accumulation of SA and NO triggers extensive transcriptional reprogramming of defense-related genes, induced biosynthesis of secondary metabolites and anti-microbial compounds, thereby protecting/steering plant growth and immunity. Transcriptional regulation of SA and NO signaling are crucial for fine-tuning important cellular and metabolic functions, thus making plant defense impervious against many pathogens. The development of an impenetrable immune response is often associated with an unavoidable trade-off in the form of active suppression of plant growth and reproduction. Therefore, we highlighted recent advancements and research to unravel transcriptional regulation of SA and NO signaling essential for fulfilling their role as defense signaling molecules. We also emphasized comprehensive knowledge related to transcriptional reprogramming of SA and NO signaling important in strengthening plant growth-immunity trade-off. We also highlighted the progress on SA and NO signaling playing an indispensable role in stimulating plant-microbe interaction to modulate crucial plant functions.